United Way Worldwide chooses new CEO. Issue 386 (13th October 2021) - Unknown
Abstract : The United Way Worldwide has selected Angela F. Williams as its next president and CEO. According to the organization, Williams will be the first woman and first African American to lead United Way's Worldwide organization. She has served as president and CEO of Easterseals since 2018.